2014
DOI: 10.3892/ol.2014.1989
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ovarian cancer cell proliferation by Pien Tze Huang via the AKT-mTOR pathway

Abstract: Pien Tze Huang (PZH) is a well-known Chinese medicine that has been used as a therapeutic drug in the treatment of a number of diseases, such as hepatocellular carcinoma and colon cancer. However, few studies have analyzed the effects of PZH on ovarian cancer cell proliferation. In the present study, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide and Transwell assays, cell cycle and apoptosis rate analyses and western blotting were conducted to investigate the effects of PZH on the proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…TCMs have received recent interest in this regard, as they have relatively few side effects and have been used for thousands of years as alternative remedies for a number of diseases, including cancer ( 7 , 8 ). The well-known TCM formula PZH has long been used in China to treat a number of cancers ( 45 , 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…TCMs have received recent interest in this regard, as they have relatively few side effects and have been used for thousands of years as alternative remedies for a number of diseases, including cancer ( 7 , 8 ). The well-known TCM formula PZH has long been used in China to treat a number of cancers ( 45 , 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Proliferation and apoptosis of cells are two critical factors that determine organism development and tissue homeostasis [ 86 , 87 ]. Precisely, it is the unrestricted proliferation and suppressed apoptosis that make cancer cells grow frantically and malignantly.…”
Section: Tcm Inhibits the Development Of The “Seed”mentioning
confidence: 99%
“…Although the mechanisms are not very clear, increasing data has shown that they maybe relate with above-mentioned regulating biomarkers to inhibit proliferation and induce apoptosis of cancer cells. The confirmed mechanisms of herb compounds and monomers acting common cancers are listed in Table 2 [ 86 , 88 , 91 , 92 , 95 , 97 , 99 – 103 ].…”
Section: Tcm Inhibits the Development Of The “Seed”mentioning
confidence: 99%
“…In CRC patients, the synthesis of UDP‐N‐acetyl‐D‐glucosamine (UDP‐GlcNAc) is increased, which is the substrate for OGT for O‐GlcNAcylation of target proteins and O‐GlcNAcylation of certain proteins may be a key factor in tumorigenesis . In addition, abnormal activation of AKT/mTOR signalling is the key factor of CRC, which leads to tumour growth and metastasis . Previous studies have shown that DDX5 can transcriptionally co‐activate AKT signaling pathway in CRC to regulate cancer progression .…”
Section: Introductionmentioning
confidence: 99%